A framework for utilizing unexplored game elements in designing learning systems - Elshorbagy, Sara Adel; Sherief, Nada; Abdelmoez, Walid (Advances in Computing and Engineering, 2022)
Gamification is defined as the use of game elements and designs in non-gaming areas and applications such as education, marketing, and healthcare. That is to facilitate and develop the engagement of users with a product or service. Researchers have found that gamified learning has the ability to improve student success, interaction, and enjoyment of courses. Recently, researchers suggested that one way to achieve that is through the personalization of students’ experiences. However, research has been focusing on a narrow group of game elements which does not ensure equal consideration when designing for different personality types. In this paper, our aim is threefold that is: to identify the unexplored game elements in the learning domain to ensure equal experiences for different personality traits; to study the utilization of the identified unexplored elements and how they can be used in relation with different personality types and learning styles to make learning tasks more desirable and enjoyable; to inform and enrich the design of gamified e-learning systems. To achieve that aim, we analyzed the literature to identify the unexplored game elements, conducted a focus group study to examine the utilization of unexplored game elements along with other contextual aspects. Then to formalize the results reached from our study and provide more systematic means for software engineers to extract useful information that can inform their designs, an ontology was implemented for that purpose. Finally, an existing gamified e-learning framework was adapted to illustrate how the formed artifacts and models interrelate to realize the research aim.